Association Between Metabolic and Obesity Phenotypes and Diabetes Risk in Children and Adolescents - Hao H; Su Y; Feng M (Diabetes, Metabolic Syndrome and Obesity)
Huiling Hao, Yanhua Su, Mei Feng Department of Endocrinology, Children’s Hospital of Shanxi, Taiyuan, Shanxi, People’s Republic of ChinaCorrespondence: Huiling Hao, Email b20160905216@stu.ccsu.edu.cnIntroduction: Diabetes is a significant public health concern worldwide, having increased rapidly in recent decades among younger generations. The correlation between metabolic/obesity phenotypes and the development of pre-diabetes in children and adolescents remains unclear.Methods: This study aimed to explore this association within a cohort of 1,524 subjects aged 7 to 18 years. Subjects were categorized into four groups based on their metabolic and obesity status: Metabolically Unhealthy with Normal Body Weight (MUNW), Metabolically Healthy Overweight/Obesity (MHO), Metabolic Healthy with Normal Body Weight (MHNW), and Metabolically Unhealthy Overweight/Obesity (MUO). Physical parameters such as body mass, as well as biochemical markers including blood pressure, fasting glucose, triglycerides, and high-density lipoprotein cholesterol, were measured.Results: A total of 61.9% of children were within the normal range for both body weight and metabolism (MHNW), while 24.4% were classified as MUNW, 5.7% as MHO, and 8% as MUO. The risks of diabetes in the MUNW and MUO groups were 8.89 and 9.18 times higher than in the MHNW group for boys, and 8.15 and 11.24 times higher for girls (P< 0.05).Conclusion: These findings suggest that abnormal metabolism, irrespective of body weight, significantly increases the risk of diabetes, while obesity alone does not predict pre-diabetes unless accompanied by metabolic dysregulation. Metabolic markers may serve as more sensitive indicators for assessing diabetes risk in this population.Keywords: Abnormal metabolism, body mass, diabetes, children and adolescents